2018
DOI: 10.1182/bloodadvances.2017013243
|View full text |Cite
|
Sign up to set email alerts
|

Hhex induces promyelocyte self-renewal and cooperates with growth factor independence to cause myeloid leukemia in mice

Abstract: Key Points• Overexpression of Hhex transcription factor blocks myeloid differentiation at the promyelocyte stage.• Hhex cooperates with growth factor independence to elicit rapid promyelocytic leukemia in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Using in situ hybridization, we indeed observed that endothelial hhex expression was increased in hhex mutants. This finding is consistent with a recent report in hematopoietic cells 39 .…”
Section: Discussionsupporting
confidence: 94%
“…Using in situ hybridization, we indeed observed that endothelial hhex expression was increased in hhex mutants. This finding is consistent with a recent report in hematopoietic cells 39 .…”
Section: Discussionsupporting
confidence: 94%
“…As reported so far, aberrantly expressed NKL homeobox genes in AML include DLX1 and DLX2 [18], HHEX [54,55], HLX [19], MSX1 [56], NANOG [57], and VENTX [20,58]. Our study added several other NKL subclass members to this list.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, TGF β signaling downregulates HHEX activity and induces an EMT that facilitates cell migration (Marcolino et al, 2020 ). HHEX induces promyelocyte self-renewal and cooperates with growth factor independence to cause myeloid leukemia in mice (Jackson et al, 2018 ). HHEX regulates the self-renewal of hematopoietic stem cell (HSC), emergency hematopoiesis, and the initiation of acute myeloid leukemia (AML) via repression of the Cdkn2a tumor suppressor locus (Jackson et al, 2017 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%